MK8617 inhibits M1 macrophage polarization and inflammation via the HIF-1α/GYS1/UDPG/P2Y14 pathway - Qian, Lingling; Chen, Xiao-qin; Kong, Deyang; Wang, Gaoyuan; Cao, Yun; Xiao, Yingchun; Cao, Jing-yuan; Zou, Chunbo (PeerJ, 2023)
Background Nonresolving inflammation is a major driver of disease and needs to be taken seriously. Hypoxia-inducible factor (HIF) is closely associated with inflammation. Hypoxia-inducible factor-prolyl hydroxylase inhibitors (HIF-PHIs), as stabilizers of HIF, have recently been reported to have the ability to block inflammation. We used MK8617, a novel HIF-PHI, to study its effect on macrophage inflammation and to explore its possible mechanisms. Methods Cell viability after MK8617 and lipopolysaccharide (LPS) addition was assessed by Cell Counting Kit-8 (CCK8) to find the appropriate drug concentration. MK8617 pretreated or unpretreated cells were then stimulated with LPS to induce macrophage polarization and inflammation. Inflammatory indicators in cells were assessed by real-time quantitative reverse-transcription polymerase chain reaction (qRT-PCR), western blot (WB) and immunofluorescence (IF). The level of uridine diphosphate glucose (UDPG) in the cell supernatant was measured by ELISA. Purinergic G protein-coupled receptor P2Y14, as well as hypoxia-inducible factor-1α (HIF-1α) and glycogen synthase 1 (GYS1) were detected by qRT-PCR and WB. After UDPG inhibition with glycogen phosphorylase inhibitor (GPI) or knockdown of HIF-1α and GYS1 with lentivirus, P2Y14 and inflammatory indexes of macrophages were detected by qRT-PCR and WB. Results MK8617 reduced LPS-induced release of pro-inflammatory factors as well as UDPG secretion and P2Y14 expression. UDPG upregulated P2Y14 and inflammatory indicators, while inhibition of UDPG suppressed LPS-induced inflammation. In addition, HIF-1α directly regulated GYS1, which encoded glycogen synthase, an enzyme that mediated the synthesis of glycogen by UDPG, thereby affecting UDPG secretion. Knockdown of HIF-1α and GYS1 disrupted the anti-inflammatory effect of MK8617. Conclusions Our study demonstrated the role of MK8617 in macrophage inflammation and revealed that its mechanism of action may be related to the HIF-1α/GYS1/UDPG/P2Y14 pathway, providing new therapeutic ideas for the study of inflammation.
Keywords: Hypoxia-inducible factor-prolylhydroxylase inhibitor; Inflammation; Glycogen synthase 1; Uridine diphosphate glucose/P2Y14 signaling pathway